Dampak Prinsip-Prinsip Dasar ASEAN Terhadap Pola Kerjasama ASEAN Menghadapi Krisis Kudeta Myanmar - Putri, Alvela; Jasmine, Putri; Salma, Riana; Bagasta, Galang; Faturrahman, M. Padhil (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
ASEAN as a regional organization has fundamental principles that underlie all activities carried out by member countries. This basic principle was recorded in the TAC (Treaty of Amity and Cooperation in South-East Asia) in 1976. However, in February 2021, one of the ASEAN member countries, Myanmar, was facing a crisis caused by a coup by the Myanmar military. ASEAN has a fundamental principle that keeps member countries from interfering with each other. However, the Myanmar crisis could affect other member countries and ASEAN cooperation. This study aims to determine the pattern of ASEAN cooperation in dealing with the Myanmar crisis under the basic principles of ASEAN. The research method used is a case study method with this type of research as qualitative research. This paper concludes that ASEAN principles which contrasting to the issues that currently occur make it difficult for ASEAN to make a foreign policy-making approach to the issue of the Myanmar military coup. In addition, this paper also concludes that to overcome the limits given by these basic principles, ASEAN takes an approach through the ASEAN Way of Diplomacy.